THE BIOLOGICAL FATHERS HAVE CIVIL RIGHTS WITH EVIDENCE AND CONVICTION OF THEIR CHILDREN - Anwar Hafidzi; Nadiyah Khalid; Rina Septiani (IAIN Manado, 2020)
This paper aims to prove that Biological Children can provide Civil Relations with their fathers if they have an apparent legal force. This study differs from other researchers in the comparative aspect of normative Law and Islamic Law. This difference lies in the Constitutional Court decision results, which states that children produced outside of marriage have a civil relationship with the mother and family of their mother, father, and family of their biological father, which can be proven by DNA testing between them. Meanwhile, according to Islamic Law, children outside of marriage (Zina) only have a civil relationship or blood relationship with the mother and the mother's family. The method used in this research is a literature review with a normative approach to the Constitutional Court decision and the Scholar's opinion on children outside of marriage (Siri). This research found that children can biologically provide civil relations with their parents if done in marriage and proven by clear legalities such as witnesses and marriage documents. The presence of a decision of the Constitutional Court is a legal assurance or defense of the human rights of a citizen, whether they have the correct data and facts to their civil relations.